1994
DOI: 10.1021/j100054a036
|View full text |Cite
|
Sign up to set email alerts
|

Redox behavior and mobility of copper ions in NaZSM-5 zeolite during oxidation

Abstract: The redox behavior and mobility of the Cu ions in Cu ion-exchanged NaZSM-5 zeolites (Cu-NaZ) during oxidation of benzyl alcohol were examined by CO adsorption, IR absorption measurement of CO adsorbed on the Cu-NaZ, and diffuse reflectance spectra measurement. The properties and oxidation state of the Cu ions in Cu ion-exchanged S i 0 2 (Cu-SiOz) were also investigated by similar methods, focusing on the comparison with those in the Cu-NaZ zeolites. The Cu-NaZ zeolites with higher degrees of Cu ion exchange we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 9 publications
(17 reference statements)
2
27
2
Order By: Relevance
“…These results are in accordance with those published by Minchev et al (2001), who found that the surface area of |Cu x |[Si y Al]-MCM-41 mesoporous solids is influenced by Cu content and by the method used during Cu impregnation. hexagonally coordinated by water molecules and O atoms found in the framework of the molecular sieves studied (Itho et al, 1994). In accordance with Moretti et al (2001), this band disappears when |Cu x.…”
Section: +2supporting
confidence: 69%
“…These results are in accordance with those published by Minchev et al (2001), who found that the surface area of |Cu x |[Si y Al]-MCM-41 mesoporous solids is influenced by Cu content and by the method used during Cu impregnation. hexagonally coordinated by water molecules and O atoms found in the framework of the molecular sieves studied (Itho et al, 1994). In accordance with Moretti et al (2001), this band disappears when |Cu x.…”
Section: +2supporting
confidence: 69%
“…The presence of bands at around 212, 256 and a broad, but weak band between 600 and 850 nm can be observed. Itho et al 23 reported that the band at 212 nm, which appears in the spectra of all samples, is related to the zeolitic support and therefore not related to the Cu-species. The band at 256 nm is attributed to Cu 2+ interacting with oxygen atoms in the zeolite structure and the band between 600 and 850 nm to Cu 2+ cations in hexagonal coordination (this band is indicated in Figure 7 between arrows) 23,24 .…”
Section: Catalyst Characterisationmentioning
confidence: 92%
“…Itho et al 23 reported that the band at 212 nm, which appears in the spectra of all samples, is related to the zeolitic support and therefore not related to the Cu-species. The band at 256 nm is attributed to Cu 2+ interacting with oxygen atoms in the zeolite structure and the band between 600 and 850 nm to Cu 2+ cations in hexagonal coordination (this band is indicated in Figure 7 between arrows) 23,24 . Although the above discussed TPR-H 2 results suggest the presence of small amounts of CuO in the |Cu x |[Si y Al]-MFI catalysts, in their DRS-UV/VIS spectra there is no band at around 890 nm, which could indicate the presence of this species 25 .…”
Section: Catalyst Characterisationmentioning
confidence: 92%
“…Alternatively, an absorption band at ca. 30,000 cm −1 could also be due to the presence of divalent copper species such as [CuOCu] 2+ , Cu 2+ O − and Cu 2+ O 2 − [40,58,60,61]. But, no clear bands at lower energy (d-d bands) are distinguished, making the presence of divalent copper species unlikely.…”
Section: Time and Temperature Dependence Of The No Decompositionmentioning
confidence: 99%